2014
DOI: 10.7860/jcdr/2014/8239.5042
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Levels of Salivary Mucin, Amylase and Total Protein in Gingivitis and Chronic Periodontitis Patients

Abstract: Background: Periodontal diseases are a group of inflammatory conditions resulting from interaction between a pathogenic bacterial biofilm and susceptible host's inflammatory response eventually leading to the destruction of periodontal structures and subsequent tooth loss. Hence, investigation of salivary proteins in individuals with periodontal diseases may be useful to enhance the knowledge of their roles in these diseases. Materials and Methods:This case-control study was conducted at A.B. Shetty Memorial I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 31 publications
(37 reference statements)
8
32
0
4
Order By: Relevance
“…In present study, we noticed elevated levels of total protein in periodontitis subjects, this increase in concentration may be attributed to modulation by extent of plasma protein exudation. Present study was in accordance with study conducted by Amita Ahire et al, Arati et al, Swati et al and Nada et al [14][15][16][17] Elevated levels of ROS levels were noted in the saliva of chronic periodontitis subjects. These elevated levels of ROS in saliva can result in imbalance between oxidants and antioxidants causing destruction of the periodontium leading to periodontitis.…”
Section: Discussionsupporting
confidence: 92%
“…In present study, we noticed elevated levels of total protein in periodontitis subjects, this increase in concentration may be attributed to modulation by extent of plasma protein exudation. Present study was in accordance with study conducted by Amita Ahire et al, Arati et al, Swati et al and Nada et al [14][15][16][17] Elevated levels of ROS levels were noted in the saliva of chronic periodontitis subjects. These elevated levels of ROS in saliva can result in imbalance between oxidants and antioxidants causing destruction of the periodontium leading to periodontitis.…”
Section: Discussionsupporting
confidence: 92%
“…Intralobular ducts normally do not provide the typical basal membrane infoldings and increased numbers of mitochondria like in striated type of ducts. [1][2][3] Saliva produced by the sublingual, submandibular, and minor salivary glands contains, for example, mucins and amylase 4 and is crucial for digestion, tasting, pH-buffering, tooth remineralization, and immune defense. 5 The clinical importance of these small glands becomes evident in the possible development of a variety of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Study by Swati Kejriwal 2014 15 recorded SAA level by kinetic assay method and found significantly higher values in gingivitis group 95.7047 U/ml, in periodontitis group 125.01 U/ml as compared to the healthy group 77.2113 U/ml as seen in Table-4: Intra-group comparison of mean PPD and CAL for group C, at baseline and after SRP using 't' test…”
Section: Kejriwal S (2014)mentioning
confidence: 99%
“…18 Thus, the high concentration of salivary α-amylase seen in present study suggests it to be an important defense molecule essential for the innate immunity in the oral cavity. 15 iii) The increased levels could partly be also due to an increased leakage of plasma proteins into saliva due to inflammation. 19 It was observed that mean SAA level was reduced, 6 weeks after the SRP in group B and C. The study by 20 compared SAA in chronic periodontitis patients before and after SRP.…”
Section: Group Mean Ohi -S ± Sd Baselinementioning
confidence: 99%